Multi-Behavioral Endpoint Testing of an 87-Chemical Compound Library in Freshwater Planarians - Zhang, Siqi (Toxicol Sci, 2019)
There is an increased recognition in the field of toxicology of the value of medium-to-high-throughput screening methods using in vitro and alternative animal models. We have previously introduced the asexual freshwater planarian Dugesia japonica as a new alternative animal model and proposed that it is particularly well-suited for the study of developmental neurotoxicology. In this article, we discuss how we have expanded and automated our screening methodology to allow for fast screening of multiple behavioral endpoints, developmental toxicity, and mortality. Using an 87-compound library provided by the National Toxicology Program, consisting of known and suspected neurotoxicants, including drugs, flame retardants, industrial chemicals, polycyclic aromatic hydrocarbons (PAHs), pesticides, and presumptive negative controls, we further evaluate the benefits and limitations of the system for medium-throughput screening, focusing on the technical aspects of the system. We show that, in the context of this library, planarians are the most sensitive to pesticides with 16/16 compounds causing toxicity and the least sensitive to PAHs, with only 5/17 causing toxicity. Furthermore, while none of the presumptive negative controls were bioactive in adult planarians, 2/5, acetaminophen and acetylsalicylic acid, were bioactive in regenerating worms. Notably, these compounds were previously reported as developmentally toxic in mammalian studies. Through parallel screening of adults and developing animals, planarians are thus a useful model to detect such developmental-specific effects, which was observed for 13 chemicals in this library. We use the data and experience gained from this screen to propose guidelines for best practices when using planarians for toxicology screens.